PRIMARY AND SECONDARY TEACHER’S PSYCHOLOGICAL WELLBEING IN MALAYSIA - Mat Zin, Nur Izzati; Sulong, Rose Manisah; Zainuddin, Zaida Nor; Ayub, Ahmad Fauzi Mohd (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The psychological well-being of teachers is a critical factor influencing not only individual health but also the effectiveness and sustainability of educational systems. Guided by Ryff’s multidimensional model of Psychological Well-Being (PWB), this study examined the levels and dimensions of psychological well-being among Malaysian teachers across primary and secondary schools. A total of 479 teachers participated in the study, and data were collected using the 42-item Ryff’s PWB scale. Descriptive statistics revealed that overall psychological well-being among Malaysian teachers was moderate to high (M = 3.8483, SD = 0.38413), with the highest mean observed in the dimension of Purpose in Life (M = 4.0653), followed by Positive Relations with Others (M = 4.0095), and Personal Growth (M = 3.9970). Autonomy registered the lowest mean (M = 3.3749), suggesting a potential area of concern. Additionally, an independent samples t-test showed no statistically significant difference in psychological well-being between primary (M = 3.8803) and secondary school teachers (M = 3.81), p = .055, though a marginal trend was observed favouring primary school teachers. The findings highlight the strengths and vulnerabilities in teachers’ psychological functioning, with implications for policy and school leadership practices aimed at promoting teacher well-being. Enhancing autonomy-supportive environments and reinforcing personal growth opportunities may serve as strategic interventions to improve overall teacher well-being and retention. These insights contribute to the increase in growing on international literature related to teachers’ mental health and provide empirical evidence from the educational context of Southeast Asian countries.